2020
DOI: 10.3390/nu12010169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nutrition on Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is characterized by sustained vasoconstriction, vascular remodeling, inflammation, and in situ thrombosis. Although there have been important advances in the knowledge of the pathophysiology of PAH, it remains a debilitating, limiting, and rapidly progressive disease. Vitamin D and iron deficiency are worldwide health problems of pandemic proportions. Notably, these nutritional alterations are largely more prevalent in PAH patients than in the general population and there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 142 publications
(204 reference statements)
1
38
0
Order By: Relevance
“…For the treatment, pharmaceutical therapies are often used primarily to result in an improvement and possibly a cure. However, the aspect of non-pharmaceutical therapy, such as exercise therapy and/or restrictive diets [34], takes an equally important contribution and is of increasing interest in current disease management [10]. Regarding other chronic diseases, physical activity was found beneficial, which was reinforced by Chia et al [35] in topical research for PAH.…”
Section: The Role Of Exercisementioning
confidence: 99%
“…For the treatment, pharmaceutical therapies are often used primarily to result in an improvement and possibly a cure. However, the aspect of non-pharmaceutical therapy, such as exercise therapy and/or restrictive diets [34], takes an equally important contribution and is of increasing interest in current disease management [10]. Regarding other chronic diseases, physical activity was found beneficial, which was reinforced by Chia et al [35] in topical research for PAH.…”
Section: The Role Of Exercisementioning
confidence: 99%
“…In addition, another condition linked to inflammation, thrombosis, endothelial alterations, and HIV infections, which can itself benefit from a nutritional intervention, is pulmonary hypertension. In particular, vitamin D, vitamin C, and iron deficiency have been observed in patients with this disease, while a diet rich in flavonoids, isoflavones, and resveratrol is associated with a slower progression of this disorder in animal models [64].…”
mentioning
confidence: 99%
“…Nutrition has also gained attention as a factor potentially influencing the Moreover, it was found that the gut microbiota is changed in a rat model of PAH (Callejo et al, 2018). This would merit further elucidation of the potential role of gut microbiota and its interplay with the diet, immune function and energy metabolism in the context of PAH (Callejo, Barberá, et al, 2020). As described in chapter 3 of this thesis, drugs can also influence gut microbiota, so the interplay between the gut and often used drugs in PAH might be an interesting topic for future research.…”
Section: Nutritional Therapy Is a Promising Emerging Field In The Treatment Of Pahmentioning
confidence: 97%
“…Other authors that reviewed studies on the presence of micronutrient deficiencies in PAH also found that iron and vitamin D deficiencies are highly prevalent in PAH patients (Callejo, Barberá, et al, 2020;Semen & Bast, 2019). However, for vitamin D there are only a few studies available with a with a small sample size.…”
Section: Nutritional Therapy Is a Promising Emerging Field In The Treatment Of Pahmentioning
confidence: 99%
See 1 more Smart Citation